Health systems characteristics: A survey of 21 Latin American and Caribbean countries - Lorenzoni, Luca (OECD Publishing, 2019)
In 2018, the Inter-American Development Bank and the OECD launched a survey to collect information on key health systems characteristics in Latin American and Caribbean (LAC) countries. This paper presents the information provided by 21 of these countries. It describes country-specific arrangements to organise the population coverage against health risks and the financing of health spending. It depicts the organisation of health care delivery, focusing on the public/private mix of health care provision, provider payment schemes, user choice and competition among providers, as well as the regulation of health care supply and prices. Finally, this document provides information on governance and resource allocation in health systems (decentralisation in decision-making, nature of budget constraints and priority setting)
Keywords: Social Issues/Migration/Health